Strategies for enhancing core capability of large-scalely operation for national telecom operators assisted by big data - Jiarui GUO; Jinwu WEI; Yunyong ZHANG (Dianxin kexue)
The research has been executed through the history of big data belonging to the international telecom operators.A splendid summary of the practical experience was indicated in four aspects,including the organization of operation,the application of operation,the platform layout and data integration.The concepts will promote national network carriers in scaling up the core operation capability,as well as the development of the future industrialization of internet by applying specifically beneficial strategies and advices.